First trimester markers of preeclampsia in twins: maternal mean arterial pressure and uterine artery Doppler pulsatility index. (6th June 2014) - Svirsky, R.; Yagel, S.; Ben‐Ami, I.; Cuckle, H.; Klug, E.; Maymon, R.
ABSTRACT Objective This study aims to evaluate the distribution of mean arterial pressure (MAP) and uterine artery Doppler pulsatility index (PI) in first trimester twins with and without preeclampsia. Method A total of 147 twins were recruited from a specialist clinic and 110 unaffected singleton pregnancies attending the same institution served as controls. MAP and Doppler PI values were expressed in multiples of the gestation‐specific median using published equations. Results Among the twins, 12 had preeclampsia and two had pregnancy‐induced hypertension. Among unaffected pregnancies, there was no significant difference in MAP levels between twins and singletons (P = 0.17, Wilcoxon rank sum test, two‐tail). However, the Doppler PI levels were highly statistically significantly lower than in singletons (P < 0.0005). MAP was unrelated to chorionicity (P = 0.46), but there was a statistically significant increase in Doppler PI among monochorionic compared with dichorionic twins (P < 0.01). In twins with preeclampsia, MAP was significantly higher than in unaffected twins (P < 0.02, one‐tail), whereas Doppler PI levels were significantly reduced (P < 0.01, two‐tail). Conclusion If first trimester screening for preeclampsia is extended to twins, a different normal median Doppler PI equation will be needed. Contrary to expectations, Doppler PI levels may not be raised in affected twins, although this needs confirmation in a larger study. © 2014 John Wiley & Sons, Ltd.